2017
DOI: 10.1039/c6re00204h
|View full text |Cite
|
Sign up to set email alerts
|

A general [18F]AlF radiochemistry procedure on two automated synthesis platforms

Abstract: The first general [18F]AIF automated radiolabelling procedure developed on the GE Tracerlab FX FN (Left) and Trasis AllInOne (Right) platforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…These promising preclinical results, the commercial availability of the precursor (GMP-grade) and the straightforward radiolabeling strategy, make [ 18 F]AlF-NOTA-octreotide an ideal candidate for imaging NET in a clinical setting. Allott et al described recently a general Al 18 F-radiochemistry procedure on two automated radiosynthetizer platforms (Trasis AllinOne® and GE TRACERlab FX FN ) and concluded that both systems have a great potential for the GMP productions of Al 18 F radiopharmaceuticals (Allott et al 2017). They successfully produced [ 18 F]AlF-NOTAoctreotide using this procedure but further optimization was required for routine clinical GMP production.…”
Section: Introductionmentioning
confidence: 99%
“…These promising preclinical results, the commercial availability of the precursor (GMP-grade) and the straightforward radiolabeling strategy, make [ 18 F]AlF-NOTA-octreotide an ideal candidate for imaging NET in a clinical setting. Allott et al described recently a general Al 18 F-radiochemistry procedure on two automated radiosynthetizer platforms (Trasis AllinOne® and GE TRACERlab FX FN ) and concluded that both systems have a great potential for the GMP productions of Al 18 F radiopharmaceuticals (Allott et al 2017). They successfully produced [ 18 F]AlF-NOTAoctreotide using this procedure but further optimization was required for routine clinical GMP production.…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication from the group describes full process automation of the approach, having been encouraged by the results of the method and the recognised requirement for automated processes in GMP production . High temperatures and a water‐miscible solvent were, again, used in the fully automated procedure which resulted in efficient radiolabelling of 2 model APPs which required single SPE‐purification of the final radiolabelled product . A clear advantage of the approach is the simplicity of the single‐vial method and ability to use commercially available aqueous [ 18 F]fluoride/H 2 O.…”
Section: Non‐site‐specific Radiolabellingmentioning
confidence: 99%
“…A clear advantage of the approach is the simplicity of the single‐vial method and ability to use commercially available aqueous [ 18 F]fluoride/H 2 O. Application of the fully automated approach to a NOTA‐derivatised octreotide, chosen for its commercial availability, achieved RCY of >45% and RCP measurements of >98% within 26 minutes …”
Section: Non‐site‐specific Radiolabellingmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, a plug-and-play radiosynthesis platform accompanied by computer software based on modular subunits can easily and flexibly be configured to implement a diverse range of radiosynthesis protocols [194]. Using such systems, the standard procedures ( 18 F-labelling, hydrolysis and purification) have been implemented for many clinically relevant 18 F-tracers [103,105,191,[195][196][197] or 18 Flabelled building blocks for labelling of macromolecules [198][199][200] and build-up syntheses [145].…”
Section: Automation Of Nucleophilic 18 F-fluorinationmentioning
confidence: 99%